2021
DOI: 10.1177/00202940211001904
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning algorithm evaluation of hypertension classification in less photoplethysmography signals conditions

Abstract: This study used photoplethysmography signals to classify hypertensive into no hypertension, prehypertension, stage I hypertension, and stage II hypertension. There are four deep learning models are compared in the study. The difficulties in the study are how to find the optimal parameters such as kernel, kernel size, and layers in less photoplethysmographyt (PPG) training data condition. PPG signals were used to train deep residual network convolutional neural network (ResNetCNN) and bidirectional long short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The proposed technique is also compared with some recent work, as presented in Table 6 . In Table 6 , it is clearly indicated that our proposed technique is better in terms of accuracy compared with [ 40 ]. However, the accuracy obtained in [ 41 ] is equal to the proposed one, and hence we added another data set and applied deep learning in the proposed work to gain more attraction.…”
Section: Resultsmentioning
confidence: 96%
“…The proposed technique is also compared with some recent work, as presented in Table 6 . In Table 6 , it is clearly indicated that our proposed technique is better in terms of accuracy compared with [ 40 ]. However, the accuracy obtained in [ 41 ] is equal to the proposed one, and hence we added another data set and applied deep learning in the proposed work to gain more attraction.…”
Section: Resultsmentioning
confidence: 96%
“…There are three indices of the results: the standard deviation (SD) of the short term of PPT or SD1 in (3), the SD of the long term of PPT or SD2 in (4), and SSR in (5).…”
Section: Poincaré Plot Analysismentioning
confidence: 99%
“…The best performing algorithm had a 92.5% accuracy. Yen et al [14] classified hypertension stages, based on PPG signals, using a Deep Residual Network, Convolutional Neural Network, and Bidirectional Long Short-Term Memory model. An accuracy of 76% was achieved in the testing data.…”
Section: Related Workmentioning
confidence: 99%